Influencias de la formación profesional y los procedimientos pedagógicos de los docentes en el aprendizaje de los estudiantes de la escuela de enfermería de la Facultad de Ciencias Químicas y de la Salud de la Universidad Técnica de Machala en el período 2013 – 2014. - Sornoza Zambrano, Azucena (2014)
Most of the professors of the UTMACH Nursing career are experts in their specialty, but they have limited pedagogical training, which negatively affects the process -docente educativo and is not in accordance with the demands of higher education , Which conceives the teacher, as an inducer of critical thinking - reflexive in students preparing them to face future professional challenges. The general objective of this work is to make a diagnosis about the pedagogical training of teachers, and based on the same elaborate a proposal of pedagogical training plan for the teachers, that contributes to improve the learning process of the students. To this end, a descriptive, cross-sectional, qualitative and applied study was carried out using the surveys and interviews as tools to obtain the data. The results showed that the main problem affecting the quality of teaching is that only 50% of teachers have a certified pedagogical training. In addition to the lack of commitment to the activity. In order to solve this problem in the work, a teacher training program is proposed, which comprises six levels, which are implemented through semi - face and distance activities, using the advantages offered by information technologies. Also included are seminars, workshops, exams etc., which are developed in person to facilitate the direct exchange between teachers in training with their tutors and teachers. The proposal allows to train the teacher from the pedagogical, specialized, educational, didactic, cultural and communicative dimensions.